A practice based longevity study on single-unit crowns. (July 2018) - Collares, Kauê; Correa, Marcos B.; Bronkhorst, Ewald M.; Laske, Mark; Huysmans, Marie-Charlotte D.N.J.M.; Opdam, Niek J.
Abstract: Objectives: This retrospective longitudinal study aimed to assess the longevity of single unit crowns placed by several dentists and to investigate risk factors associated with crown failures. Methods: From patient files, longevity of 3404 full crown restorations placed in 1557 patients by 8 Dutch dentists between 1996 and 2011 were analyzed. Annual failure rates (AFRs) were calculated and variables associated with failure (success and survival of crowns) were assessed by multivariate Cox-regressions analysis with shared frailty for patients. Results: Most of crowns were PFM (63.8%) placed in molars (58.1%) and non endodontically treated teeth (65.4%). The observation time of restorations varied from 3 weeks to 11 years with a mean of 7 years, resulting in a mean AFR at 11 years of 2.1% and 0.7% for success and survival of crowns, respectively. Among dentists a relevant variation for type of interventions was observed with AFR varying between 1.2% and 3.5%. The most significant risk factor for failure of crowns was the presence of an endodontic treatment, resulting in Hazard ratios of 1.31 for success [95%CI 1.07–1.61] and 1.89 [95%CI 1.35–2.65] for survival of crowns. Tooth type, tooth position (jaw) and gender showed also a significant influence on success of crowns. For survival, increase in patients' age results in a higher risk for failure. Conclusions: Overall, crowns placed by a selected group of dentist showed a good to acceptable success and survival rates, mainly dependent from the practice. The presence of an endodontically treated tooth was a significant risk factor leading to more failures.